2016
DOI: 10.1016/j.drugpo.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of compulsory drug treatment: A systematic review

Abstract: Background Despite widespread implementation of compulsory treatment modalities for drug dependence, there has been no systematic evaluation of the scientific evidence on the effectiveness of compulsory drug treatment. Methods We conducted a systematic review of studies assessing the outcomes of compulsory treatment. We conducted a search in duplicate of all relevant peer-reviewed scientific literature evaluating compulsory treatment modalities. The following academic databases were searched: PubMed, PAIS In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
119
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 58 publications
3
119
0
3
Order By: Relevance
“…A systematic review 19 of compulsory inpatient and outpatient treatment strategies showed little evidence that compulsory drug treatment is effective in promoting abstention from drug use or in reducing criminal recidivism. This review did not, however, compare the effectiveness of CDDCs relative to evidence-based treatment, such as voluntary medical treatment with opioid agonist therapies.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review 19 of compulsory inpatient and outpatient treatment strategies showed little evidence that compulsory drug treatment is effective in promoting abstention from drug use or in reducing criminal recidivism. This review did not, however, compare the effectiveness of CDDCs relative to evidence-based treatment, such as voluntary medical treatment with opioid agonist therapies.…”
Section: Introductionmentioning
confidence: 99%
“…39 There is no evidence that these centres are effective in treating drug dependence. 40 Rather, detention in such centres often leads to the denial or inadequate provision of medical care. 39 41 In China and Vietnam, compulsory drug detention centres are historically grounded in a system of "re-education through labour" that has detained dissidents and activists.…”
Section: Poor Record Of Compulsory Treatmentmentioning
confidence: 99%
“…42 Detainees have been subject to human rights abuses, including extrajudicial and indefinite detention, physical abuse, and torture. [30][31][32][33][34][35][36][37][38][39][40][41][42][43] For example, in Cambodia, children with drug dependence were detained against their will, routinely beaten (sometimes with electrical cables), forced to work, and were subject to other abuses, including sexual abuse. 44 Evidence from compulsory drug detention centres is sparse but has supported concerns about the efficacy of mandatory treatment techniques.…”
Section: Poor Record Of Compulsory Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indiscriminate mass round-ups of individuals in these scenes have been followed by their compulsory detention or hospitalization, a counterproductive measure explicitly condemned by United Nations agencies 7 and assessed as both ineffective and potentially associated with various human rights violations and harms, as shown in a recent systematic review 8 .…”
mentioning
confidence: 99%